Pengaruh Emotional Intelligence dan Work Load terhadap Work Engagement dengan Occupational Well-Being sebagai Variabel Mediasi pada Perawat di Cikampek - Omar Rizki Rasyabi; Yudi Nur Supriadi; Renny Husniati (Gapenas Publisher, 2026)
This study aims to analyze the influence of emotional intelligence and workload on work engagement, with occupational well-being as a mediating variable, among hospital nurses in the Cikampek region. The study employed a quantitative approach using an explanatory research design. Data were collected through a questionnaire distributed to 150 nurses selected using probability sampling with the simple random sampling method. Data analysis was performed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) via the SmartPLS 3 software. The results showed that emotional intelligence had a positive and significant effect on occupational well-being (? = 0.621; p < 0.001) and work engagement (? = 0.394; p < 0.001). Conversely, work load has a significant negative effect on occupational well-being (? = -0.377; p < 0.001) and work engagement (? = -0.366; p < 0.001). Occupational well-being was also found to have a positive effect on work engagement (? = 0.293; p < 0.001). Furthermore, occupational well-being mediates the effects of emotional intelligence and workload on work engagement. These findings indicate that enhancing emotional intelligence, managing workload appropriately, and improving occupational well-being are key factors in strengthening nurses’ work engagement. The results of this study are expected to serve as a foundation for hospital management in designing human resource management policies aimed at improving the quality of healthcare services